A NEURAL NETWORK PREDICTION MODEL FOR SURFACEFINISH IN TURNING PROCESS (Journal of Engineering, 2024)
This paper presents a neural network based surface finish Prediction model in turning operation .Orthogonal cutting tests were performed on mild steel using H.S.S cutting tool with differentcutting parameters cutting speed ,feed and nose radius of the cutting tool . The collected data wasused to train feed forward back propagation neural network. The developed model has been testedto preclict surface finish for various cutting conditions. The model was found to be powerful &capable of accurate surface finish prediction for the range it had been trained but the accuracydeteriorated as the cutting conditions were changed significantly'